2019
DOI: 10.1186/s13550-019-0534-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parathyroid 11C-choline PET protocol for localization of parathyroid adenomas in patients with primary hyperparathyroidism

Abstract: Purpose To evaluate the optimal tracer uptake time, the minimal amount of radioactivity and the inter-observer agreement for 11 C-choline positron emission tomography/computed tomography (PET/CT) in patients with primary hyperparathyroidism (pHPT). Methods Twenty-one patients with biochemically proven pHPT were retrospectively studied after injection of 6.3 ± 1.2 MBq/kg 11 C-choline. PET data of the first nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
12
1
1
Order By: Relevance
“…Most studies on choline PET in the detection of hyperfunctioning parathyroid glands use fluorine-18 rather than carbon-11 although others have used 11 C-Choline [ 8 , 18 , 19 , 20 , 21 ]. However, there is presumably no difference between the two tracers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on choline PET in the detection of hyperfunctioning parathyroid glands use fluorine-18 rather than carbon-11 although others have used 11 C-Choline [ 8 , 18 , 19 , 20 , 21 ]. However, there is presumably no difference between the two tracers [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 C-choline PET/CT was performed as described previously by Noltes et al [ 19 ]. In short; patients had to fast for six hours while drinking one liter of water, tea or coffee without milk and sugar prior to the PET/CT procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In the first five patients, PET/ CT images were taken directly after injection of a median dose of 556 MBq (range 510-635 MBq) 11 C-choline until 40 to 60 min postinjection. After optimizing our imaging protocol [19], all subsequent patients were scanned dynamically 20 min after injection of a median dose of 410 MBq (range 360-440 MBq) for 10 min. All images were iteratively reconstructed using three iterations, 21 subsets with 5 mm FWHM Gaussian filter, including time of flight and resolution modelling.…”
Section: C-choline Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Noltes et al set the optimal tracer uptake time at 20 min post-injection because adenoma choline uptake remains constant from 20 min onwards. Moreover, the same authors suggested a median administered dose of 6.3 MBq/kg and a scanning time for at least 5 min for [ 11 C]Choline PET/CT [34].…”
Section: Discussionmentioning
confidence: 99%